Bark production of generalist and specialist species across savannas and forests in the Cerrado. (18th January 2023) - Chiminazzo, Marco Antonio; Bombo, Aline Bertolosi; Charles-Dominique, Tristan; Fidelis, Alessandra
Abstract: Background and Aims: Bark allows species to survive fire, protecting their inner tissues and allowing new branches to resprout from aerial buds. Thus, bark production is likely to be selected with aerial bud protection in fire-prone ecosystems. By considering the coexistence of fire-prone and fire-free ecosystems, in addition to the different impacts of flames on different growth forms, in this study we tested whether: (1) species from areas with higher fire frequencies have a faster bark production; (2) bark growth rate differs between trees and shrubs; (3) generalists adjust their bark production according to their environment (fire-prone or fire-free ecosystems); and (4) fast bark production results in better aerial bud protection. Methods: We sampled two different types of forests and savannas in the Cerrado and registered every woody individual with height between 1.5 and 3 m tall (directly exposed to the flames). For the 123 species registered, we sampled three different individuals in each vegetation type where the species occurred to assess their bark production and aerial bud protection. We then checked, for each species, their preferred habitat (savanna and forest specialists or generalists) and their predominant growth form. Key Results: A minimal threshold of 0.13 mm per growth unit of bark production differentiated woody communities from savannas and forests. Shrubs and trees did not differ in terms of bark growth rate, despite being exposed to the flames in a different manner. Generalist species in savannas were able to produce bark above the threshold. However, when these species were in forests they produced bark below the threshold. Finally, a higher bark growth rate accounted for a better aerial bud protection. Conclusions: Generalist species are likely to be capable of displaying plasticity in their bark production, which could be important for their success in contrasting ecosystems. The relationship between aerial bud protection and bark growth rate suggests that bark production plays an important role in protecting the dormant buds, in addition to being selected in fire-prone ecosystems.